PERANCANGAN ANTARMUKA CHATBOT EDUKATIF UNTUK SISTEM TANYA JAWAB SDN KALIDERES 13 PETANG - Eryca Dhamma Shanty; Georgia Sugisandhea; Viny Christanti Mawardi (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2025)
The development of artificial intelligence (AI) has the potential to enhance the effectiveness of learning; however, limitations in infrastructure and the understanding of teachers and students remain obstacles to its implementation in elementary schools. SDN Kalideres 13 Petang, with 314 students from various socio-economic backgrounds, faces challenges in improving effective interactions between students and teachers. The goal of this community service activity is to introduce and assist in the implementation of the educational chatbot EduBuddy as an interactive medium in the learning process. EduBuddy is designed based on a Large Language Model (LLM) and Command R technology, allowing the chatbot to respond to students' questions automatically, quickly, and relevantly. The activities were conducted through socialization, training, and technical assistance for teachers, as well as guidance in using the chatbot for students. Teachers gained skills in integrating the chatbot into teaching activities, while students were directed to utilize it as an interactive learning medium. The results of the activity showed an increase in student engagement, expanded access to information, and significant support for teachers in delivering content. Evaluation was conducted through questionnaires and classroom observations, which indicated positive acceptance from both teachers and students. It is hoped that the success of this activity can serve as a model for digital transformation in elementary education and encourage the broader application of AI technology in the world of education.